Mapping Analysis of Personal Protective Equipment Usage as an Effort to Reach Zero Accident at Ponorogo Hospital - Rindang Diannita (Universitas Airlangga, 2022)
Introduction: One of the efforts to reduce the risk of occupational accident and occupational diseases is awareness regarding the importance of the safety and health of workers in hospitals, which is also a top priority in hospitals during a pandemic situation. The application of health protocols and the use of Personal Protective Equipment (PPE) are the main lines of defense against the risk of disease and occupational accident. So that the use of Personal Protective Equipment (PPE) is very important, especially for workers during a pandemic. The purpose of this study was to analyze the mapping of the use of Personal Protective Equipment (PPE) with the incidence of occupational accident. Methods: The research used was an analytic observational type using a cross sectional approach, besides that the researchers conducted a survey of the conditions in the hospital. With a sample of 179 respondents in all parts of the hospital. Results: There is an effect of the use of PPE on the incidence of work accidents and it is necessary to have a mapping of PPE, such as gloves, safety shoes, surgical glasses, surgical gown, apron, mask, face shield, head protection, safety helmet, safety shoes, body harness, fire-resistant clothing, fire-resistant helmet, fire-resistant goggles, and fire-resistant gloves. Conclusion: Control is needed in the form of procurement of Personal Protective Equipment at Hospital X, including face shields, aprons, gloves, masks, head protectors, and safety shoes.